Acceptance of Online Education by Undergraduate Students During the Covid-19 Pandemic: A Case Study from Kerman, Iran - Milad Ahmadi Gohari; Abedin Iranpour; Salahodin Rakhshani Rad; Moghaddameh Mirzaee; Ali Akbar Haghdoost (Kerman University of Medical Sciences, 2023)
Background: Online education has become more vastly recognized as a powerful educational tool after the Covid-19 pandemic. It provides educational opportunities that were not previously possible because of time or place restrictions.Objectives: This study investigated the factors influencing students' acceptance of online learning systems during the Covid-19 pandemic.Methods: The study sample comprised 435 students from Kerman University of Medical Sciences. We used the external technology acceptance model (TAM) to determine the acceptance of online education systems by undergraduate students during the Covid-19 pandemic. Partial least square structural equation modeling (PLS-SEM) was used to check the model hypotheses. P-values less than 0.05 were considered statistically significant.Results: In this study, 65% of the participants were men. The mean score for the items in the questionnaire was 53.1±19.3. The constructs of perceived ease of use and perceived usefulness had a significant effect on students' attitudes, and students' attitudes and perceived usefulness strongly influenced their behavior in using the online education system.Conclusion: The results of this study show that the perceived ease of use and perceived usefulness of the online education system indirectly affect students' behavior in using online education. Thus, educational policymakers at universities can emphasize the ease of learning and especially the easy use of mobile phones when choosing an online education system. In addition, the creation and expansion of the necessary infrastructure can facilitate student use of online education.